Improving the quality of aster Posyandu in stunting prevention strategy and health independence at Bantul - Solikhah, Efa Wakhidatus; Puriyanto, Riky Dwi; Irham, Lalu Muhammad (Universitas Ahmad Dahlan, 2024)
Posyandu is the front line in public health services, especially for mothers, children, and the elderly at the village level. However, along with the development of the era and the needs of the community, there are significant challenges related to the limitations of the tools and the effectiveness of the services provided. This study aims to identify and implement innovations in improving tools and improving services at the Aster Posyandu located in Srihardono, Pundong, Bantul, Special Region of Yogyakarta (DIY). Through a participatory approach, this community service activity involves Posyandu cadres and the local community in the process of evaluating service management, improving, and training in the use of digital health tools. The results of this intervention showed a significant increase in the quality of service, especially in terms of measurement accuracy, service time efficiency, and community satisfaction. In addition, innovations in the management system and service flow have also succeeded in reducing queues and accelerating the process of recording health data. Improvements in tools and service innovations at Posyandu have a positive impact on increasing health independence, as well as strengthening the role of Posyandu as the spearhead of health services at the village level.